2006
DOI: 10.2337/diaclin.24.3.115
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia in Type 1 and Type 2 Diabetes: Physiology, Pathophysiology,and Management

Abstract: IN BRIEF The threat and incidence of hypoglycemia is the major limiting factor in intensive glycemic control for both type 1 and type 2 diabetes. This article reviews the physiology of the normal counterregulatory responses to hypoglycemia and the deficient counterregulatory defenses that occur in patients with diabetes. Treatment paradigms for establishing good glycemic control while limiting hypoglycemia are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 45 publications
1
116
1
7
Order By: Relevance
“…For example, disease management of diabetic patients is aimed at reducing blood sugar levels and should therefore reduce emergency admissions for acute hyperglycaemic complications. But excessively aggressive management of blood sugar can increase the risk of admissions for hypoglycaemic coma (Briscoe and Davis, 2006). The targeting of patients with specified chronic conditions may also divert GP efforts away from other types of patients and increase their risk of hospitalization.…”
Section: General Practice Disease Management and Hospital Costmentioning
confidence: 99%
“…For example, disease management of diabetic patients is aimed at reducing blood sugar levels and should therefore reduce emergency admissions for acute hyperglycaemic complications. But excessively aggressive management of blood sugar can increase the risk of admissions for hypoglycaemic coma (Briscoe and Davis, 2006). The targeting of patients with specified chronic conditions may also divert GP efforts away from other types of patients and increase their risk of hospitalization.…”
Section: General Practice Disease Management and Hospital Costmentioning
confidence: 99%
“…Normally, the body's response to hypoglycemia consists of suppression of insulin release and secretion of glucagon and pancreatic polypeptides from the pancreas and the release of epinephrine, norepinephrine, cortisol and growth hormone (Briscoe & Davis, 2006). Glucagon and epinephrine are the primary hormones that protect the human body against hypoglycemia.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…The symptoms of hypoglycemia can be categorized as neurogenic or neuroglycopenic (Briscoe & Davis, 2006). Neurogenic or autonomic symptoms are triggered by an actively falling glucose, which causes the individual to realize they are having a hypoglycemic event.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…In T1DM, insulin deficiency is often accompanied by the loss of glucagon secretory response to hypoglycemia. Furthermore, insulin therapy causes even more degradation in the functionality of other counterregulatory hormones (Briscoe & Davis (2006)), and consequently, results in higher possibility for hypoglycemic risk. Different artificial pancreas studies have demonstrated that glucagon infusion significantly reduces the risk of insulin-induced hypoglycemia in T1DM (Castle et al (2010);El-Khatib et al (2009;; Ward et al (2008)).…”
Section: Hypoglycemia In Closed-loop Artificial Pancreasmentioning
confidence: 99%